2016
DOI: 10.1093/nar/gkw271
|View full text |Cite
|
Sign up to set email alerts
|

The DBHS proteins SFPQ, NONO and PSPC1: a multipurpose molecular scaffold

Abstract: Nuclear proteins are often given a concise title that captures their function, such as ‘transcription factor,’ ‘polymerase’ or ‘nuclear-receptor.’ However, for members of the Drosophila behavior/human splicing (DBHS) protein family, no such clean-cut title exists. DBHS proteins are frequently identified engaging in almost every step of gene regulation, including but not limited to, transcriptional regulation, RNA processing and transport, and DNA repair. Herein, we present a coherent picture of DBHS proteins, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
299
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 227 publications
(328 citation statements)
references
References 182 publications
9
299
2
Order By: Relevance
“…The DBHS family shares highly conserved tandem N-terminal RRMs, a NonA/paraspeckle domain (NOPS) and a C-terminal coiled-coil (93). SFPQ binds wide range of nucleic acids and can be found in the pre-assembled spliceosome complex.…”
Section: Abnormally Spliced (As) Mrnas In Amlmentioning
confidence: 99%
See 1 more Smart Citation
“…The DBHS family shares highly conserved tandem N-terminal RRMs, a NonA/paraspeckle domain (NOPS) and a C-terminal coiled-coil (93). SFPQ binds wide range of nucleic acids and can be found in the pre-assembled spliceosome complex.…”
Section: Abnormally Spliced (As) Mrnas In Amlmentioning
confidence: 99%
“…SFPQ binds wide range of nucleic acids and can be found in the pre-assembled spliceosome complex. However, SFPQ is not an essential member of spliceosome, but rather act as a molecular scaffold and involve cotranslational and alternative splicing (93). Mutations in SFPQ and in the nonclassic regulators of mRNA processing CTCF and RAD21 have been discovered in 10% of AML patients in a mutually exclusive manner (94).…”
Section: Abnormally Spliced (As) Mrnas In Amlmentioning
confidence: 99%
“…They are predominantly defined by colocalization of dynamic and multifunctional RNA-binding proteins, such as splicing factor, proline-and glutamine-rich (SFPQ), non-POU domain-containing octamer-binding protein (NONO) or paraspeckle component 1 (PSPC1). These factors belong to the Drosophila behavior/human splicing (DBHS) protein family that forms a dynamic scaffold with the long noncoding RNA NEAT1 (Bond and Fox, 2009;Clemson et al, 2009;Fox et al, 2005;Knott et al, 2016). The major function of paraspeckles is nuclear retention of mRNA that contains doublestranded (ds)RNA structures at the 3′ untranslated region (UTR), which are generally formed by adenosine-to-inosine edited inverted repeats (Fox and Lamond, 2010).…”
Section: Paraspecklesmentioning
confidence: 99%
“…Besides being essential paraspeckle components, DBHS proteins act as molecular scaffolds that synergistically associate with a broad spectrum of transcription factors, DNA and RNA. This allows the scaffold to promote transcription initiation, elongation and termination, to facilitate co-transcriptional processing -in particular splicing -and to regulate mRNA transport and cytosolic trafficking (Knott et al, 2016). In addition, paraspeckles may mediate regulatory crosstalk with the nucleolus: paraspeckle proteins localize to perinucleolar caps when RNA Pol II transcription is inhibited, and it has been observed that PSPC1 shuttles between paraspeckles and nucleoli (Fox and Lamond, 2010).…”
Section: Paraspecklesmentioning
confidence: 99%
See 1 more Smart Citation